From free to civilized trade: a European perspective. Issue 3 (2nd July 2016) - Kapeller, Jakob; Schütz, Bernhard; Tamesberger, Dennis
Abstract: In the context of unfettered international competition, free trade tends to undermine basic moral concepts such as justice, dignity, and fairness. Therefore, we suggest moving to a new understanding of markets in international trade, which we call 'civilized markets'. A civilized market tries to ensure that free entrepreneurship and open markets are eventually compatible with those basic and universal values that also serve as moral cornerstones of the European project. In order to accomplish a civilized market, we propose to establish a new European institution with a mandate to set and enforce minimum standards for goods sold on the European market.